2022
DOI: 10.1091/mbc.e21-08-0414
|View full text |Cite
|
Sign up to set email alerts
|

Plectin linkages are mechanosensitive and required for the nuclear piston mechanism of three-dimensional cell migration

Abstract: The nucleus can hinder cell migration through three-dimensional environments due to its size and rigidity. We find that plectin cross-links vimentin and actomyosin filaments in response to substrate rigidity and these cross-links help to pull the nucleus forward in cells moving through the narrow openings in extracellular matrices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Cell studies have shown evidence for regulation by phosphorylation of sites like serine 4642 in the C-terminal extremity (Bouameur et al 2013, Foisner et al 1996, 1991) and by oxidation and nitrosylation of cysteines in plectin’s IFBD (Spurny et al 2007). Finally, a recent study showed that the association between plectin and vimentin is mechanosensitive and requires actomyosin contractility (Marks et al 2022). Our reconstitution assay could be used to test whether this mechanosensitivity is intrinsic to plectin, for instance to its force-sensing plakin domain (Daday et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cell studies have shown evidence for regulation by phosphorylation of sites like serine 4642 in the C-terminal extremity (Bouameur et al 2013, Foisner et al 1996, 1991) and by oxidation and nitrosylation of cysteines in plectin’s IFBD (Spurny et al 2007). Finally, a recent study showed that the association between plectin and vimentin is mechanosensitive and requires actomyosin contractility (Marks et al 2022). Our reconstitution assay could be used to test whether this mechanosensitivity is intrinsic to plectin, for instance to its force-sensing plakin domain (Daday et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In cells, IFs are crosslinked to F-actin and MTs via large crosslinking proteins including members of the plakin family such as plectin (Bouameur et al 2014, Mohammed et al 2020, Wiche and Winter 2011). Electron microscopy imaging and proximity ligation assays in cells have shown that plectin forms both IF-IF crosslinks and crosslinks of IFs to F-actin and MTs (Foisner et al 1995, 1988, Marks et al 2022, Svitkina et al 1996, Wiche and Baker 1982). In motile mesenchymal cells, plectin crosslinks vimentin filaments to F-actin stress fibers (Jiu et al 2015, Marks et al 2022) and to F-actin found at the base of invadopodia (Schoumacher et al 2010, Yoneyama et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vimentin intermediate filaments are required for the nucleus to be pulled forward by actomyosin contractility through 3D CDM ( Figure 2A ) ( Petrie et al, 2017 ). The cytoskeleton crosslinking protein plectin connects the cytoplasmic F-actin network in front of the nucleus to the basket of vimentin intermediate filaments that surround the nucleus in response to substrate rigidity ( Marks et al, 2022 ). Specifically, this network is assembled in response to soft substrates and requires NMII activity, consistent with mechanosensing by the classical rigidity-sensing machinery.…”
Section: The Plasticity Of Nmii During 3d Cell Migrationmentioning
confidence: 99%